Childhood experiences of separation and divorce : reflections from young adults - Kay-Flowers, Sue (Policy, 2019)
Drawing on the qualitative research findings, this book develops a new framework to provide a useful analytical tool for academics and practitioners working with children and families to make sense of young people's experiences of parental separation and divorce and puts forward suggestions for improving support for children in the future.